Thomas Jefferson's Bible - Holowchak, M. Andrew (De Gruyter, 2018)
This volume is the first full-length book that offers a critical investigation into the composition of Jefferson's Bible. In it, the author looks critically not only at what Jefferson includes, but also at what he chose to exclude in an effort to uncover the principles that Jefferson employed in selecting and deselecting verses. In addition to providing a full text of Jefferson's Bible, this study places these documents within a historical, philosophical and theological context that illuminates their significance and relevance to our time
10.1515/9783110619843
Keywords: American Christianity; Amerikanisches Christentum; Kritische Ausgabe; Textkritik; Textual Criticism; Thomas Jeffereson; Thomas Jefferson; critical edition